2015
DOI: 10.1021/jp511741f
|View full text |Cite
|
Sign up to set email alerts
|

Ab Initio Studies of Segregation, Ordering, and Magnetic Behavior in (Fe–Pt)n, n = 55 and 147: Design of Fe75Pt72 Nanoparticle

Abstract: We report results of a systematic study on atomic and electronic structure of 55-atom and 147-atom Fe−Pt nanoparticles with different compositions using ab initio calculations. Our results on 55-atom nanoparticles suggest icosahedral structure and segregation of Pt on the surface to be favorable. Also, there is a tendency for Fe−Pt ordering on the surface and maximization of the unlike bonds similar to the bulk, while the core is made of pure Fe 13 , giving it a core−shell structure. Using these considerations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…The core–shell arrangement can start with small nanoclusters; for example, it has been shown that various compositions of PtCu nanoalloys of up to 14 atoms resemble core–shell structures, which are favorable due to the strain released by allocating the smaller atom on the core region . Furthermore, the stability trends related to the preference of certain elements for the surface or core regions can hold for a range of compositions, for example, PtFe nanoalloys are generally more stable with all or most Pt atoms on the surface region. …”
Section: Introductionmentioning
confidence: 99%
“…The core–shell arrangement can start with small nanoclusters; for example, it has been shown that various compositions of PtCu nanoalloys of up to 14 atoms resemble core–shell structures, which are favorable due to the strain released by allocating the smaller atom on the core region . Furthermore, the stability trends related to the preference of certain elements for the surface or core regions can hold for a range of compositions, for example, PtFe nanoalloys are generally more stable with all or most Pt atoms on the surface region. …”
Section: Introductionmentioning
confidence: 99%
“…The effects of nanoalloy particle size, physical phase, and other parameters on the FePt nanoalloys structure and properties have also been investigated with simulation methods. [44][45][46] For example, an embedded atom model with a classical molecular dynamics simulation method has been applied to study the size of 2-6 nm and temperature of 300-2700 K on the FePt nanoalloys' stability and local structural evolutions. 47 The simulation results reveal that the most stable atomic configurations are the deformed bcc and deformed icosahedron structures regardless of the liquid state at 1700 K or the glassy state at 300 K. As for the structure revolution, the phase separation at about 300 K and at the nano scale would result in the core-shell structure with Fe-rich shell and Pt-Fe-rich core, which means the FePt nanoalloys are core-shell structures instead of homogenous element distribution.…”
Section: Controllable Synthesis Of Fe-based Nanoalloysmentioning
confidence: 99%
“…This leads to the conclusion that nanoparticle-containing devices have a lot of potential for storing data. 2 On inspecting the properties of Fe, Pt, Co, Cu, etc, it can be understood that the magnetic properties of FeO and CuCo nanoalloys suit the best for this purpose.…”
Section: Introductionmentioning
confidence: 99%